Polite Requests of Indonesian Learners of FLE and French Native Speakers: An Interlanguage Study - Elvi Syahrin; Tengku Silvana Sinar; Eddy Setia; Nurlela Nurlela (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study anchored in the field of Interlanguage Pragmatic (ILP). The approach taken is speech act based. The investigation focuses on realization of polite requests produced by Indonesian learners of Français langue étrangère (FLE) (henceforth abbreviated as ILF) and native speakers of French (henceforth abbreviated as NSF). The model used for the investigation is the Cross-Cultural Speech Act Realization Project (CCSARP) model formulated by Blum-Kulka et al. (1989), modified by Warga (2005) and Bae (2012). The model applied to the analysis of the data is based on three politeness systems of social relationship between speaker and addressee proposed by Scollon and Scollon (2001). Data was be collected by using Written Discourse Completion Test (WDCT). Six out of twelve request situations formulated by Reiter (2000) categorized into each politeness system were selected to be analyzed. The WDCT were tested to 20 ILF; 1 learner of Universitas Negeri Medan and 19 learners of Universitas Negeri Jakarta. The 20 participants are those who are certified of Diplôme d'études en langue française (DELF) of B2 level (advanced level). As the baseline data of the study, the e-mailed data of 20 NSF were also collected. The study found that there is a preference of Indonesian learners of FLE and native speaker of French to use Conventional Indirect strategy in their requests. This strategy, even realized in slightly different number of use, was highly used and considered to be the most polite request by the two groups.